Aux sources des inégalités face au numérique, le rapport des enseignants du secondaire aux technologies numériques : retrait, appropriation ou partage ? - Isabelle Danic; Thierry Lefort; Laurent Mell
The IDÉE research studies the establishment of Digital Pedagogical Cooperatives (CPN) in Bretagne (France), a continuing education system initiated by the Rector, which is part of a living-lab system in order to provide teachers with space and time to share pedagogical experiences, produce resources and provide peer-to-peer training, particularly in relation to their use of digital technologies. From a quantitative and qualitative survey, we examine the relationship of secondary school teachers to digital technologies in the context of their teaching practices by lighting three scales: institutional discourses prescribing the use of digital technology; its use in the classroom; the acquisition of skills through training and collaboration between teachers.